A New Process for the Synthesis of Budesonide 21-Phosphate and Evaluation in a Murine Model of Inflammation - Angela Corvino; Elisabetta Granato; Antonia Scognamiglio; Ferdinando Fiorino; Francesco Frecentese; Elisa Magli; Elisa Perissutti; Vincenzo Santagada; Giuseppe Cirino; Ida Cerqua; Rocco Pavese; Antonio Petti; et al. (Molecules)
In this study, a new and straightforward process for the preparation of budesonide 21-phosphate (Bud-21P) and its disodium salt (Bud-21P-Na2) is described. The method results in a yield comparable to those obtained by diphosphoryl chloride, but it is more manageable, less expensive, and safer. The new compounds are characterized by better water solubility compared to the parent compound. Moreover, they have been evaluated for their anti-inflammatory activity and the obtained results clearly evidence that Bud-21P and Bud-21P-Na2 retained anti-inflammatory activity like the parent compound budesonide (Bud) in mice with cutaneous induced edema.